In vitro equine embryo production using air-dried spermatozoa, with different activation protocols and culture systems - Alonso, Ana Elisa (2014)
The aim of this work was to evaluate the use of air-dried spermatozoa for in vitro production of equine embryos and verify if sperm extract activation and in vivo culture improve in vitro embryo production. Cooled spermatozoa (control) and air-dried spermatozoa stored for 2, 14 or 28 days were used for ICSI sperm extract, or ionomycin was used for oocyte activation, and embryos were in vitro or in vivo (in mare′s oviduct) cultured for 7 days. With in vitro culture, cleavage rate was higher when activating with sperm extract (P < 0.05). No differences in embryo development were seen between the two activation treatments nor between storage periods (P > 0.05). Blastocysts were obtained with cooled spermatozoa, and morulae were achieved using in vivo culture with 28-day storage spermatozoa and ionomycin-activated oocytes. When in vivo culture was performed, sperm DNA fragmentation was assessed using the sperm chromatin dispersion test and did not show statistical correlation with cleavage nor embryo recovery rates. In conclusion, equine embryos can be produced using air-dried spermatozoa stored for several weeks. Sperm extract activation increased cleavage rates but did not improve embryo development. In vivo culture allowed intrauterine stage embryos to be achieved.